Children's agency in reducing poverty and environmental risk : case study of drop-in- centre, care-net development and support organisation - Lombard, A. (Antoinette) (University of Pretoria, 2023)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2022.